Komodifikasi Anak Dalam Program Acara Reality Show Di Trans Tv - Agustinus Kardiman; Haryo Windratno (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2016)
This research is attempted to uncover forms, processes and ideologies associated with the commodification of children at those impressions by takes perspective of a critical discourse analysis of the commodification of children in the program